DESIGN OF PIT X BASED ON PRODUCTION TARGETS USING MINE SCHEDULING CONCEPT AT PT Y - Ismail, Ardhan; Mochamad Gaharu Dida Devedo; Pontus, Albertus Juvensius; Thomas , Anita oktoviana L.P.G.M. (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2025)
Pit design in surface mining requires a systematic approach that considers operational capacity and efficiency to ensure optimal production target achievement. In the actual condition of the second quarter of 2025, pit X design at PT Y was carried out manually using a trial-and-error method. This method was time-consuming and less flexible to parameter changes, and caused significant deviations from production targets, with overburden reaching 110%, coal only 89%, and stripping ratio increasing to 4.19 from the target of 3.39. This study aims to develop pit design based on Mine Scheduling Concept using SPRY Scheduler software to improve operational effectiveness and efficiency. An applied quantitative method was implemented by integrating reserve data from Minescape, heavy equipment parameters including availability, utilisation, and hourly rate, as well as a mining calendar aligned with operational conditions in the third quarter of 2025. The results show that the generated pit design achieves production targets with very high accuracy: overburden of 4,093,991 Bcm with a deviation of -0.02%, coal of 1,206,663 MT with a deviation of 0.00%, and a stripping ratio of 3.39 as targeted. The application of SPRY Scheduler produces measurable, accurate, and adaptive pit designs without trial-and-error processes, supporting efficient and sustainable mine planning.